Chatting about chatting - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Many employers in Macau expect their employees to have received higher education (HE). This returns to the endless question of what HE is for; is it for job knowledge and skills acquisition, attitude development, thinking abilities, creativity, problem solving, how to learn, or what? What and whose knowledge?
Section: Macau Business